Application of Joyful Learning Method in Learning Tafsir Tarbawi for Islamic Religious Education (PAI) Students - Saiful Lutfi; Moh Fauzan; Surawan Surawan; Dedi Arman (Jurnal Studi Guru dan Pembelajaran, 2025)
Tafsir Tarbawi learning in higher education often experiences methodological obstacles so that the learning atmosphere becomes monotonous and less interesting, especially for millennials and Z generations who need interactive and fun learning methods. This study aims to examine the application of the Joyful Learning approach and its impact on student motivation and understanding. The research used a qualitative method with a case study approach to third semester students of the Islamic Education Study Program at UIN Palangka Raya. Data were collected through participatory observation during the learning process, semi-structured interviews with selected students, and document analysis in the form of teaching materials and student assignments. Data were analyzed using thematic analysis techniques to identify patterns and main themes related to the effectiveness of the Joyful Learning approach. Data validity was maintained through triangulation of data sources and methods, as well as member checking with research participants. The results showed that the application of Joyful Learning - through ice breaking activities, mind-mapping discussions, creative presentations, and interactive quizzes - succeeded in creating a lively and participatory classroom atmosphere. The positive impact can be seen from the increase in enthusiasm, contextual understanding of tarbawi verses, critical thinking skills, and students' emotional and intellectual engagement. This research contributes to the development of innovative and humanist Tafsir Tarbawi learning methods and opens up opportunities for further research with a wider scope and more comprehensive methods.